2015
DOI: 10.1016/j.bone.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic calcification and risk of fracture among older women — The SOF study

Abstract: Data concerning the link between severity of abdominal aortic calcification (AAC) and fracture risk in postmenopausal women are discordant. This association may vary by skeletal site and duration of follow-up. Our aim was to assess the association between the AAC severity and fracture risk in older women over the short- and long-term. This is a case-cohort study nested in a large multicenter prospective cohort study. The association between AAC and fracture was assessed using Odds Ratios (OR) and 95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 54 publications
2
15
1
Order By: Relevance
“…This could be because of the disease for which they were prescribed (CVD) or because of the hypotensive effects of taking nitrates. Because persons with CVD manifest by aortic calcification, they may also have greater fracture risk . The study from claims data supports the limited medications data from our cohort.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This could be because of the disease for which they were prescribed (CVD) or because of the hypotensive effects of taking nitrates. Because persons with CVD manifest by aortic calcification, they may also have greater fracture risk . The study from claims data supports the limited medications data from our cohort.…”
Section: Discussionsupporting
confidence: 79%
“…Because persons with CVD manifest by aortic calcification, they may also have greater fracture risk. (28) The study from claims data supports the limited medications data from our cohort. Attributing risk to medication prescribing may suffer from bias by indication, making it quite difficult to discern the disease from the medication used to treat the disease, as the causal risk factor.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, AAC was associated with fracture, independent of conventional fracture risk factors, suggesting a novel potentially non‐BMD mechanism. A previous nested case‐cohort study in older women ( n = 951, mean age approximately 72 years) found that an AAC24 score >4, assessed from DXA‐derived LSIs, was not associated with a risk of nonvertebral fractures after 4 or 15 years, but was associated with a higher 4‐year risk of vertebral fractures and 5‐year risk of hip fractures . A prospective study of older men ( n = 5400, aged ≥65 years) found severe AAC was associated with a high risk of hip fracture, but not nonhip fractures .…”
Section: Discussionmentioning
confidence: 99%
“…A previous nested case-cohort study in older women (n = 951, mean age approximately 72 years) found that an AAC24 score >4, assessed from DXA-derived LSIs, was not associated with a risk of nonvertebral fractures after 4 or 15 years, but was associated with a higher 4-year risk of vertebral fractures and 5-year risk of hip fractures. (37) A prospective study of older men (n = 5400, aged ≥65 years) found severe AAC was associated with a high risk of hip fracture, but not nonhip fractures. (36) These discordant differences between the current study and the above-mentioned studies may have been caused by the cut-point selected, the fracture ascertainment methods, or population differences.…”
Section: Discussionmentioning
confidence: 99%
“…Results are reported per one-unit increase in ABI, per increase in one average standard deviation increase of CD, and for 1 mm increase in thickness of both walls of the aorta (AWT). To determine whether the association of subclinical CVD with fracture risk weakened with duration of follow up (22) analyses were repeated with 5 years follow up and 10 years follow up. To put our CD findings into context, we also estimated the risk of clinical CVD outcomes for an increase of one average standard deviation increase of CD.…”
Section: Methodsmentioning
confidence: 99%